2010
DOI: 10.1038/sj.bjc.6605591
|View full text |Cite
|
Sign up to set email alerts
|

The G-protein-coupled formylpeptide receptor FPR confers a more invasive phenotype on human glioblastoma cells

Abstract: BACKGROUND: The G-protein-coupled formylpeptide receptor (FPR) that mediates chemotaxis of phagocytic leucocytes induced by bacterial and host-derived chemotactic peptides is selectively expressed by highly malignant human gliomas and contributes to tumour growth and angiogenesis. As invasion of surrounding normal tissues is one of the important features of tumour malignancy, we investigated the function of FPR in the invasive behaviour of human glioblastoma cells. METHODS: Cells (FPR þ and FPR À ) were isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 32 publications
4
47
0
Order By: Relevance
“…The significance of our study is that to our knowledge it provides the first example of a non-hematopoietic setting for FPR1 expression linked directly to a biological phenotype in vivo, namely severe degeneration of lens structure in aging Fpr1 Ϫ/Ϫ mice. 4 Our characterization of the human FPR1 in human lens epithelial cells suggests that this property of Fpr1 may also be relevant to humans. How FPR1 functions to maintain the lens is not yet known.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The significance of our study is that to our knowledge it provides the first example of a non-hematopoietic setting for FPR1 expression linked directly to a biological phenotype in vivo, namely severe degeneration of lens structure in aging Fpr1 Ϫ/Ϫ mice. 4 Our characterization of the human FPR1 in human lens epithelial cells suggests that this property of Fpr1 may also be relevant to humans. How FPR1 functions to maintain the lens is not yet known.…”
Section: Discussionmentioning
confidence: 99%
“…work is consistent with a direct role in the lens for FPR1 in lens homeostasis, as evidenced by aging Fpr1 Ϫ/Ϫ mice, which develop severe cataracts. 4 At first glance the evidence for functional expression of the receptor in this cell line appears straightforward and consistent. 1) Full-length FPR1 mRNA was amplified and sequenced by PCR using specific primers and knocked down using specific siand shRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also found that F2 could significantly inhibit the migration and invasion of fMLF (a FPR1 agonist)-induced U87 cells due to its partial agonist action on formyl peptide receptor 1 (FPR1) (10). FPR1 is a membrane receptor overexpressed in U87 cells, regulates the cell growth, survival, migration and invasion (11,12). Moreover, an in vivo study showed that repeated administration of F2 to mice had no adverse effects (13).…”
Section: Introductionmentioning
confidence: 99%